NONCONVENTIONAL METHOD OF COLD PREPARING THE CELLULAR GLASS (Nonconventional Technologies Review, 2023)
The preparation at room temperature of cellular glass from recycled residual glass and fly ash was made adopting a manufacturing method recently applied in the case of geopolymer foam. Sodium perborate in aqueous solution as a blowing agent and detergent as a surfactant have been experimentally tested in several versions. The optimal cellular glass product was obtained by mixing 2.6 % sodium perborate, 0.2 % surfactant, and 7.6 % water addition. The characteristics of this expanded product were: density of 0.65 g·cm-3, heat conductivity of 0.134 W·m-1·K-1, and compression resistance of 1.2 MPa, being satisfactory for its application as heat insulating product in construction. The main advantage of this method was the product manufacture in satisfactory quality conditions without supplementary energy consumption and greenhouse gas emissions (CO2) into the atmosphere, like in the case of the usual manufacturing cellular products at high temperature.
Keywords: cellular glass; room temperature; sodium perborate; surfactant; thermal insulation material